2019
DOI: 10.1111/crj.13133
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial ultrasound‐guided mediastinal lymph node forceps biopsy in patients with negative rapid‐on‐site‐evaluation: A new step in the diagnostic algorithm

Abstract: Background Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) provides a high diagnostic yield in lung cancer, but the yield for benign conditions and lymphoma is lower. The material obtained by EBUS‐TBNA is limited by the lack of histopathological samples in some cases. The current ‘expanded’ aims of mediastinal lymph node (MLN) sampling are both an accurate diagnosis and adequate material for ‘targeted’ processing in malignant and benign disease. The sample obtained with the 21/22G … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…However, the outer diameter of both needles is identical, and this supposition will require further study. Mehta et al used a flexible electrocautery knife to create a tract for the forceps with a successful penetration of the bronchial wall [ 20 ]. This might be a proper solution to overcome this limitation in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the outer diameter of both needles is identical, and this supposition will require further study. Mehta et al used a flexible electrocautery knife to create a tract for the forceps with a successful penetration of the bronchial wall [ 20 ]. This might be a proper solution to overcome this limitation in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, Herth et al demonstrated that using a 1.5 mm mini-forceps to obtain tissue for diagnosis of enlarged mediastinal LAD is a safe and feasible technique, which provided a diagnosis in 86% of cases [ 19 ]. Recently, Mehta et al showed promising results in a small cohort of 30 patients using the 1.5 mm mini-forceps from Olympus [ 20 ]. The aim of the present study was to investigate the DY, safety, and feasibility of EBUS-TBFB using the 1.5 mm mini-forceps in addition to EBUS-TBNA as compared to standard EBUS-TBNA as a standalone technique for diagnosis of mediastinal/hilar LAD or masses in a bicentric study with a large cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Mehta et al described a novel transbronchial forceps biopsy (TBFB) approach for mediastinal lymphadenopathy sampling in their research. They suggested that BML such as sarcoidosis and TB, which are difficult to diagnose, should primarily be performed with ROSE accompanied EBUS; and recommended an algorithm that requires performing TBFB before surgery for cases with negative results 30 …”
Section: Discussionmentioning
confidence: 99%
“…Later, Herth et al applied this technique via EBUS guidance using 19‐gauge needles to create a tract for mini‐forceps and the yield was 88% [9]. Subsequently, many studies have demonstrated a yield of 91–97% via IFB without any increase in time or any significant adverse events [10–12].…”
Section: Discussionmentioning
confidence: 99%